Prognostic impact of CD109 expression in myxofibrosarcoma. Issue 8 (28th May 2015) - Emori, Makoto; Tsukahara, Tomohide; Murata, Kenji; Sugita, Shintaro; Sonoda, Tomoko; Kaya, Mitsunori; Soma, Tamotsu; Sasaki, Mikito; Nagoya, Satoshi; Hasegawa, Tadashi; Wada, Takuro; Sato, Noriyuki; et al.
<x xml:space="preserve">Abstract</x> Background CD109, a TGF‐β co‐receptor, is reported to be preferentially expressed during the early stages of tumorigenesis in several carcinoma types. Myxofibrosarcoma is one of the most common soft‐tissue sarcomas found in elderly patients. This study aimed to elucidate the impact of CD109 expression in myxofibrosarcoma on prognosis and recurrence. Methods Immunohistochemical staining for CD109 was performed on archival specimens from 37 patients. The Fisher exact test was used to evaluate association between CD109 expression and other clinicopathological features. Survival analysis was performed using Kaplan–Meier curves, and the prognostic significance was evaluated using the log‐rank test. Multivariate analysis of factors was performed using Cox regression analysis. Results CD109 overexpression was significantly associated with surgical stage and distant metastasis (P = 0.00499, and 0.011, respectively). The frequency of CD109 overexpression was approximately 10% and CD109 overexpression was significantly associated with decreased overall survival (P = 0.004). Five‐year overall survival rates 77% and 0% for CD109‐negative and CD109‐positive patients, respectively. In multivariate analysis, CD109 overexpression was the only independent risk factor for poor outcome (P = 0.02; hazard ratio, 10.64; 95% confidence interval, 1.47–76.91). Conclusions Immunohistochemical CD109 expression in myxofibrosarcoma was associated with poor prognosis. J. Surg. Oncol. 2015 111:975–979. © 2015 Wiley Periodicals, Inc.